Future MEDIC: Medical Student–Led Healthcare Career Exploration Program for Underserved Middle School Students - Sydney Sharp; Meeti Mehta; Rachel Weger; Chiazam Omenyi; Thuy Bui; Catherine Rebitch (The University of Alabama, 2023)
Future Medical Education and Development Introductory Course (Future MEDIC) is a medical student-led school program designed to inspire primary school students in underserved communities by sharing a passion for medicine and healthcare careers. Through hands-on activities-including physical examination workshops, an on-site airport introduction to flight medicine, and interactive demonstrations with a patient simulator-26 eighth-grade students were empowered to actively explore the world of healthcare. To assess the impact of Future MEDIC on students' knowledge and interest in healthcare careers, we administered pre- and post-surveys, informal exit interviews, and participation prizes. Survey responses were analyzed with a Mann Whitney U test for significance. There was a significant increase (p = 0.01) from pre- to post-survey about "I enjoy learning about how the body works." Yet there was also a significant decrease (p = 0.03) from pre- to post-survey about "In the future, I am interested in working in healthcare or medicine." Despite enjoying the activities and content of the Future MEDIC program, students did not have an increased interest in entering the healthcare field. Although interest in entering the healthcare field was not increased, Future MEDIC was a rewarding and fun experience for students to partake in, and an opportunity to create a multidimensional view of the healthcare field.